Microbiome and Allergic Diseases - Pascal, Mariona; Perez-Gordo, Marina; Caballero, Teresa; Escribese, Maria M.; Lopez Longo, M. Natividad; Luengo, Olga; Manso, Luis; Matheu, Victor; Seoane, Elena; Zamorano, Miguel; Labrador, Moisés; Mayorga, Cristobalina (Frontiers in Immunology, 2018)
Allergic diseases, such as respiratory, cutaneous and food allergy, have dramatically increased in prevalence over the last few decades. Recent research points to a central role of the microbiome, which is highly influenced by multiple environmental and dietary factors. It is well established that the microbiome can modulate the immune response, from cellular development to organ and tissue formation exerting its effects through multiple interactions with both the innate and acquired branches of the immune system. It has been described at some extent changes in environment and nutrition produce dysbiosis in the gut but also in the skin, and lung microbiome, inducing qualitative and quantitative changes in composition and metabolic activity. Here we review the potential role of the skin, respiratory and gastrointestinal tract microbiomes in allergic diseases. In the gastrointestinal tract, the microbiome has been proven to be important in developing either effector or tolerant responses to different antigens by balancing the activities of Th1 and Th2 cells. In the lung, the microbiome may play a role in driving asthma endotype polarization, by adjusting the balance between Th2 and Th17 patterns. Bacterial dysbiosis is associated with chronic inflammatory disorders of the skin, such as atopic dermatitis and psoriasis. Thus, the microbiome can be considered a therapeutical target for treating inflammatory diseases, such as allergy. Despite some limitations, interventions with probiotics, prebiotics and/or synbiotics seem promising for the development of a preventive therapy by restoring altered microbiome functionality, or as an adjuvant in specific immunotherapy.